Fundamental of entrepreneurship (ETR300) : Le Patisserie / Ahmad Solihin Ahmad Fauzi ... [et al.] - Ahmad Fauzi, Ahmad Solihin; Jemien, Luqman Afiq; Ahmad, Ainul Ammar; Dzulkifli, Ahmad Iqbal; Khalid, Muhammad Faisal (2009)
Our bakery shop café is called Le Patisserie that means The Bakery. The business is formed under the Business Registration Act 1956 (Amendment 1978) and Procedures of Business Registration 1957 where we form a paltnership. The company is commencing on the Ist of Jan 2010 and it is located at the Padungan area of Kuching. The management team consists of five person and they are the General Manager,Marketing Manager, Operation Manager, Administration Manager and Financial Manager. Each of them has their own strength and specialty. The General Manager of Le Patisserie is a person with great vision that looks for every opportunity there is and thinks outside of the box by being creative and innovative. With various working experience in his hand as a young entrepreneur, he always work hard and giving up is not an option for him. Next, is the Marketing Manager who holds the key of attracting customer to and expand our bakery shop. He is a person who is very skilled in public relation where the an of persuading is his specialty. Identifying the customer needs and wants will be no problem for him.